1998
DOI: 10.1021/jp972956a
|View full text |Cite
|
Sign up to set email alerts
|

EPR Studies Associated with the Electrochemical Reduction of C60 and Supramolecular Complexes of C60 in Toluene−Acetonitrile Solvent Mixtures

Abstract: Electron paramagnetic resonance (EPR) studies at 295 K of the radical anion of buckminsterfullerene (C60 •-) generated electrochemically by bulk-controlled potential electrolysis of neutral C60 in mixed toluene−acetonitrile solvents (5−20% v/v acetonitrile with 0.1−0.2 M n-Hex4NPF6 or n-Bu4NPF6 as the supporting electrolyte) have shown that at least three different forms of C60 •- exist in solution. The radical anions have different g values and can thus be detected by EPR spectroscopy in the form of single li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Substantial negative shifts in redox potentials can be observed when C 60 is complexed by calixarenes, presumably because fulleridestabilizing solvent dipoles are excluded from the immediate solvation sphere. 79 Reductive electrochemistry is frequently reported as part of the routine characterization of derivatized fullerenes. In an early systematic study, Suzuki and co-workers 80 showed that the usual effect of derivatization is to make the fullerene somewhat more difficult to reduce (0.1-0.3 V), although some electropositive addenda such as silyl groups, quaternary nitrogen centers, 81 or organocynanides 82 can move the redox in a positive direction.…”
Section: E1mentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial negative shifts in redox potentials can be observed when C 60 is complexed by calixarenes, presumably because fulleridestabilizing solvent dipoles are excluded from the immediate solvation sphere. 79 Reductive electrochemistry is frequently reported as part of the routine characterization of derivatized fullerenes. In an early systematic study, Suzuki and co-workers 80 showed that the usual effect of derivatization is to make the fullerene somewhat more difficult to reduce (0.1-0.3 V), although some electropositive addenda such as silyl groups, quaternary nitrogen centers, 81 or organocynanides 82 can move the redox in a positive direction.…”
Section: E1mentioning
confidence: 99%
“…There is no convincing evidence that environmental influences or supramolecular interactions can bring about such a dramatic change in signal characteristics. Studies with calixarenes show that complexation of C 60 -leads to a loss of the broad signal 362 and some of the sharp signal, 79 but this is most easily explained by the effects of spin coupling in noncovalent aggregates. The removal of the (t 1u ) 1 degeneracy of C 60 -, sufficient to change the broad signal into a sharp signal, can be accomplished by the formation of a persistent covalent bond to one or more carbon atoms.…”
Section: Origins Of Sharp Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation provides the opportunity to examine equilibration between the two triplets, especially since the isolated triplets are relatively long-lived in deoxygenated solution. Furthermore, C 60 has high electron affinity [30] and should enter into electron-transfer reactions with the excited-singlet state of Bodipy. By linking together these units through a short spacer and building in some degree of orthogonality at the linkage, we might anticipate [12] that charge recombination within the initially-formed radical ion pair would favour triplet formation.…”
mentioning
confidence: 99%
“…Explanations as to the identity of the sharp signals, generally present in <2% of the total number of spins, have included (i) strong ion pairing between C 60 ž and the supporting electrolyte cation used during electrochemical reduction experiments, 1 (ii) the presence of the C 60 2 paramagnetic species, 2b (iii) impurities in the C 60 , 3b,5e (iv) a percentage of a thermally excited state of C 60 ž , 5a (v) a reaction between C 60 ž and * Correspondence to: R. D. Webster, Research School of Chemistry, Australian National University, Canberra, ACT 0200, Australia; e-mail: webster@rsc.anu.edu.au O 2 to form C 60 O 2 ž , 7 (vi) presence of a dimer radical 8d and (vii) a reaction between C 60 ž and low levels of impurities in the solvent to form substituted fullerene radicals. 10 The interpretation of the broad and sharp signals became even more complicated when the conclusion that the narrow linewidth signals were present in only a small percentage of the total number of spins was challenged by several groups who reported conditions where only narrow linewidth signals were obtained. 8, 9 Stasko and coworkers 8 detected two sharp linewidth signals and were the most contentious in their assignment of one of the sharp signals as the real C 60 ž radical, with the second narrow ESR signal being assigned as a radical dimer, C 60 2 2 .…”
Section: Introductionmentioning
confidence: 99%